Agter elke man: Onderweg na inklusiewe taalgebruik in die Afrikaanse kerklied - Vermeulen, Ockie C. (HTS teologiese studies, 2016)
This article discusses the lack of inclusive language in the Liedboek van die kerk, which still remains the official hymnal of the Afrikaans Reformed churches in South Africa. Because there seems to be a general misconception about inclusive language, especially in this particular religious context, I will argue that the use of inclusive language will not only help to counteract the current identity crisis the church is experiencing (referring to matters such as the role of the woman, Belhar and sexuality), but will also reflect Christ’s theology of inclusivity during his time on earth. A broader understanding of the God image, rooted in biblical hermeneutics, is imperative and should be incorporated in the text of the Afrikaans hymn. I will argue that this inclusive spirituality may also lead to greater spiritual well-being of all Christians in the Afrikaans Reformed churches. This paper is critical qualitative research and arguments from the feminist theology will be interpreted and applied to the Afrikaans context.Keywords: Inclusive language; Afrikaans church; hymn; marginalised;